2018
DOI: 10.1002/jcp.26782
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized breast matrix as bioactive microenvironment for in vitro three‐dimensional cancer culture

Abstract: Breast cancer (BC) is a leading cause of cancer-related death in women with unsatisfactory survival rates. Advances in the understanding of the genetic basis of BC provide the opportunity to develop gene-based medicines capable of treating metastatic diseases. Here, we first demonstrated efficient tissue engineering approaches applied to normal breast and BC extracellular matrix (ECM) starting from decellularized human biopsies to generate a three-dimensional (3D) bioactive model with the sodium lauryl ether s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…And we hypothesized that it may be suitable for human cancer tissues. In our previous studies, we confirmed that the decellularized scaffold with SDS solution from human breast cancer tissues would promote the cell migration and proliferation in vitro (Qin. et al, 2018).…”
mentioning
confidence: 61%
“…And we hypothesized that it may be suitable for human cancer tissues. In our previous studies, we confirmed that the decellularized scaffold with SDS solution from human breast cancer tissues would promote the cell migration and proliferation in vitro (Qin. et al, 2018).…”
mentioning
confidence: 61%
“…But, the 2D conventional cell culture systems has been questioned because of potential changes in morphology and gene expression, often resulting in distortions in cell behavior and biological functions of cultured cells as compared with cells in natural organisms and tissues (Fang & Eglen, ; Huang et al., ; Jin et al., ). As for the animal model, the animals model has many uncontrollable factors such as endogenous growth factors and lack of an immune system (Jin et al., ).To better get the cell morphology, behavior and functions, the concept of 3D cell culture was proposed, that is cell growth in a 3D environment with sufficient and multidirectional cell–cell interactions mimicking the in vivo architecture of natural organs and tissues (Achilli, Meyer, & Morgan, ; Kehr, ). The 3D cell culture model is providing new insights into tumor biology and also in differentiation, tissue organization, and homeostasis (Kelm, Timmins, Brown, Fussenegger, & Nielsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies of cell behavior in normal and cancerous tissue-derived dECM were also performed to determine the roles of cancerous ECM. Jin et al compared the behavior of the MCF-7 cell line in dECM that was derived from normal and cancerous breast tissues [68]. They demonstrated that the proliferation of MCF-7 cells was decreased in cancerous dECM compared with normal dECM.…”
Section: Examples Of Decm Utilized For Cancer Researchmentioning
confidence: 99%